MYTHS OF SECURITY AND LIFE COMFORT IN THE POEM KEPADA UANG BY JOKO PINURBO: A ROLAND BARTHES SEMIOTIC STUDY - Alena Ardinda; Ayu Setiyo Putri; Septia Uswatun Hasanah; Heru Prasetyo (FKIP Universitas Lampung, 2026)
This study aims to describe the representation of money in the poem Kepada Uang by Joko Pinurbo through Roland Barthes’ semiotic approach. The research focuses on the levels of denotation, connotation, and myth to reveal the social and ideological meanings contained in the poem. This study employed a qualitative descriptive method with data collection techniques through library research and textual analysis of diction, symbols, and imagery in the poem. The results show that money in the poem is not merely interpreted as an economic transaction tool, but also represented as a symbol of life security, emotional comfort, bodily well-being, and the continuity of modern human existence. At the denotative level, the poem presents images of houses, bodies, beds, twilight, and childhood as representations of the lyrical subject’s simple life. At the connotative level, these symbols develop meanings related to protection, life struggles, nostalgia, and human vulnerability. Meanwhile, at the myth level, the poem reflects the social construction of modern society that positions money as a determinant of security, comfort, and human dignity. This study concludes that the poem Kepada Uang contains a subtle social criticism of modern life, where humans depend on economic sufficiency to achieve peace and stability. Through the symbols of home, body, and childhood nostalgia, Joko Pinurbo portrays how the relationship between humans and money has entered emotional and existential dimensions. This study is expected to contribute to the development of contemporary Indonesian literary semiotics and serve as a reference for understanding social and ideological meanings in literary works.